LATE MESOZOIC CARBONATITES OF WESTERN TRANSBAIKALIA: ISOTOPIC-GEOCHEMICAL CHARACTERISTICS AND SOURCES - Nikiforov A.V.; Yarmolyuk V.V.; Kovalenko V.I.; Ivanov V.G.; Zhuravlev D.Z. (My University, 2002)
Carbonatites in the western Transbaikalia rift area have a mid-Early Cretaceous age (130-120 Ma) and comprise lavas, tuffs, dikes, and veins, which are commonly associated with alkaline and subalkaline gabbroids and syenites. Compared to the basalts, which predominate in the volcanic area, the rocks of these carbonatite associations have higher concentrations of Ba, Pb, LREE, and Sr at much lower contents of Nb and Ta. The oxygen and carbon isotopic composition of the carbonatites (their varieties not affected by secondary processes have δ 18O from 6.0 to 10.7%‰ and δ 13C from -4.1 to -6.5%‰) is generally consistent with the mantle genesis of the rocks. The Sr and Nd isotopic composition of rocks from the carbonatite associations varies from ( 87Sr/ 86Sr) 0 = 0.7052 at ε Nd = -1.6 for tephrites to ( 87Sr/ 86Sr) 0 = 0.7059 at ε Nd = -6.4 for carbonatites from large bodies. These variations seem to have been produced by the mixing of two isotopically heterogeneous sources. A model is proposed for the genesis of the carbonatite associations that takes into account their trace-element and isotopic characteristics. It is hypothesized that mantle metasomatism under the effect of fluids, whose composition was similar to that of the carbonatites, resulted in the enrichment of LREE, St, Ba, and Pb in the mantle source and brought about the derivation of the carbonatite phases proper. The melting of this mantle gave rise to carbonatite, silicate-carbonate, and silicate (alkaline gabbroid) melts, whose further evolution and interaction led to the origin of a wide spectrum of rocks of the carbonatite association in western Transbaikalia.
Keywords: Mesozoic; Mesozoic; Мезозой